A quantitative risk analysis by using interval type-2 fuzzy FMEA approach: the case of oil spill - Akyuz, Emre; Celik, Erkan (Informa UK Limited, 2018)
Risk assessment in maritime domain is one of the most cited topics since maritime transportation poses potential hazard for human life, marine environment and property. To mitigate risk and enhance...